Peran Terminal Seruni Dalam Sistem Transportasi Perkotaan Kota Cilegon - Fitriyadi, Fitriyadi (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2016)
Cilegon is one of the National Activity Centre (PKN) in Banten Province. As PKN, Cilegon generate movement from out of town towards Cilegon, either using AKAP/AKDP buses and urban transportation from the place of origin. Many AKAP/AKDP bus passengers fell in the shadow of the terminal, while the urban transport passengers from the outside get into the city of Cilegon and drop off passengers . The number of outer urban transport operating in Cilegon Cilegon City area adds to congestion in Jalan Sultan and Jalan Ahmad Yani Ageng Tirtayasa , especially at rush hour. Therefor, the Government of Cilegon Municipality then implement the construction of SeruniTerminal, officially put into operation on April 1, 2013. With the expected Seruni terminal buses no longer drop off passengers at the terminal shadow, and urban transport outside the city of Cilegon not get into town. Positivistic approach and methods used in this study is a quantitative method , as well as some analysis used : (1) the analysis of the characteristics of SeruniTerminal, (2) analysis of traffic volume in Seruni Terminal, (3) analysis of urban transport route network in Cilegon, and (4) policy analysis for development of The Seruni Terminal, is expected to answer the research question, namely : " the role of Seruni Terminal in the urban transport system in Cilegon Municipality? "The results obtained from this study is the lack of Seruni Terminal has a role in urban transport systems in Cilegon. To enhance the role, it’s can be done with urban transport route A.01 Cilegon-Anyer and Merak-Cilegon M.01 directed toward Seruni Terminal, and/or the addition of a new trajectory Cilegon-JLS. Therefor, Seruni Terminal is expected to increase the role of the movement in serving urban communities in Cilegon.